Development of Android-Based Gamification Media Design for Personal Letters and Formal Letters Material in Grade VII - Oktaviana, Diana; Zisca Diana, Purwati (International Proceedings of Nusantara Raya, 2023)
This research aims to describe the development of gamification Android-based media design related to the teaching material of personal letters and formal letters in Grade VII of junior high school. The research method used in this study is Research and Development with the ADDIE research design, which stands for Analysis, Design, Development, Implementation, and Evaluation. The results of this research show that the Android-based learning media developed for personal letters and formal letters in Grade VII of junior high school are suitable for use in school learning. This learning media can help students understand the material more easily, increase their interest in learning, boost their motivation by presenting engaging and non-boring media, and provide benefits to students by offering enjoyable games that are not monotonous. This application is also beneficial for teachers as it facilitates the delivery of teaching materials and serves as a new innovation for teachers to continually develop their creativity by utilizing available technology and adapting it to the students' needs in line with the current era. Therefore, Android-based learning media can be an alternative learning tool that can be applied by teachers in Indonesian language learning in Grade VII.